2010
DOI: 10.1136/pgmj.2010.102475
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo cardiomyopathy: a diagnostic challenge

Abstract: The frequency of the diagnosis of takotsubo cardiomyopathy has increased rapidly over the past few years, possibly due to increasing awareness among cardiologists. At initial presentation the diagnosis remains a challenge because of the close similarity between the presentation of takotsubo cardiomyopathy, and that of ST elevation myocardial infarction (STEMI). Recognition of salient aspects of the medical history at presentation are important in order to organise further appropriate investigations such as ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 77 publications
0
52
2
1
Order By: Relevance
“…With the exception of cardiogenic shock at the time of first diagnosis in these patients in literature, short, medium and long-term prognoses have been reported to be close to excellent [8,18]. Even if left ventricle function is severely impaired on first presentation when diagnosis is made, recovery starts within a few days and with return to a normal state within a few months, normal functions have been reported to be maintained [8,19]. In the current case, cardiac functions started to improve within 12 hours and the supportive treatments were terminated.…”
Section: Recurrent Left Ventricular Dysfunction Accompanied Bymentioning
confidence: 88%
“…With the exception of cardiogenic shock at the time of first diagnosis in these patients in literature, short, medium and long-term prognoses have been reported to be close to excellent [8,18]. Even if left ventricle function is severely impaired on first presentation when diagnosis is made, recovery starts within a few days and with return to a normal state within a few months, normal functions have been reported to be maintained [8,19]. In the current case, cardiac functions started to improve within 12 hours and the supportive treatments were terminated.…”
Section: Recurrent Left Ventricular Dysfunction Accompanied Bymentioning
confidence: 88%
“…8 Many mechanisms are postulated to explain this phenomenon, but the most plausible is a rise in catecholamine levels and decreased blood flow in the myocardial microcirculation. 9 Right ventricular dysfunction may occur in approximately 25% of patients. This typically occurs in more severe cases, and patients may require IABP support.…”
Section: Discussionmentioning
confidence: 99%
“…Betablockade is recommended after recovery of myocardial function to prevent recurrence of TC. 9 The prognosis of TC is generally favourable, although fatal cases have been reported due to ventricular free-wall rupture. 11 Recurrence has been reported as high as 11%.…”
Section: Discussionmentioning
confidence: 99%
“…Uchida et al also observed elevated levels of plasma epinephrine and norepinephrine in patients with stress-induced cardiomyopathy (Uchida et al, 2010). The plasma half-life of epinephrine is only 3 min (Zeb et al, 2011, as cited in Ferreira & Vane, 1967, so measurement of catecholamines should be conducted at the time of symptom onset.…”
Section: Laboratory Findingsmentioning
confidence: 99%